Early Identification of HIV Infection Among Adolescents in Primary Care Center: A Case Study - Lindayani, Linlin; Octaviani, Putri Hilda; Al Freadman Koa, Apryadno Jose; Dian Angraenin (Window of Health : Jurnal Kesehatan, 2025)
Adolescents are at high risk for HIV transmission due to exploratory behaviors and risky activities. Early identification of HIV infection is crucial to prevent transmission, as it interrupts the transmission chain through awareness of one's HIV status. This study aimed to explore the implementation of adolescent-centered HIV early detection services in primary care. A qualitative case study design was employed, involving in-depth interviews and document analysis at a public health center in Central Bandung. A purposively selected nurse, with 15 years of experience managing the HIV program, served as the key informant. Data were collected through semi-structured interviews and analyzed using content analysis techniques to identify key themes, categories, and codes. Six themes emerged: (1) VCT service procedures; (2) community health initiatives; (3) collaboration with external institutions; (4) adolescent engagement strategies; (5) barriers to adolescent testing; and (6) factors facilitating testing. Although the VCT protocol was comprehensive and included pre- and post-counseling, fear of a positive diagnosis. While the VCT model at the primary care level is aligned with national HIV prevention strategies, its effectiveness for adolescents is limited by low participation and social resistance. Integrating case-based learning in nursing education, enhancing peer-based outreach, and strengthening adolescent-friendly health services are recommended to improve early HIV detection and care linkage for youth.